I’ve looked at gut from both sides now: Gastrointestinal tract involvement in the pathogenesis of SARS-CoV-2 and HIV/SIV infections - Pandrea, Ivona; Brooks, Kelsie; Desai, Rahul P.; Tare, Minali; Brenchley, Jason M.; Apetrei, Cristian (Frontiers in Immunology, 2022)
The lumen of the gastrointestinal (GI) tract contains an incredibly diverse and extensive collection of microorganisms that can directly stimulate the immune system. There are significant data to demonstrate that the spatial localization of the microbiome can impact viral disease pathogenesis. Here we discuss recent studies that have investigated causes and consequences of GI tract pathologies in HIV, SIV, and SARS-CoV-2 infections with HIV and SIV initiating GI pathology from the basal side and SARS-CoV-2 from the luminal side. Both these infections result in alterations of the intestinal barrier, leading to microbial translocation, persistent inflammation, and T-cell immune activation. GI tract damage is one of the major contributors to multisystem inflammatory syndrome in SARS-CoV-2-infected individuals and to the incomplete immune restoration in HIV-infected subjects, even in those with robust viral control with antiretroviral therapy. While the causes of GI tract pathologies differ between these virus families, therapeutic interventions to reduce microbial translocation-induced inflammation and improve the integrity of the GI tract may improve the prognoses of infected individuals.